Investigation of the 5-hydroxymethylyfurfural value and antioxidant properties of Kazdaği Fir cone syrup - Karacaoğlan, Volkan; Bayıl Oguzkan, Sibel; Selvi, Bedrettin; Ünal, Sabri; Bakır, Temel Kan (Cankiri Karatekin Universitesi, 2024)
Background and aims Cone syrup, unlike cone molasses, is a food product prepared without adding beet sugar. The use of high temperatures in the production of syrups and molasses causes the formation of 5-Hydroxymethylfurfural (HMF), which causes serious toxic effects on the human body, from glucose, fructose aldose and ketose monosaccharides. Although pine cone syrup is just becoming widespread in our country, it is a new food that is in high demand during the winter months. Therefore, in the study, HMF levels, sugar content, phenolic content and antioxidant levels in Kastamonu local cone syrup prepared without adding beet sugar were experimentally determined. Methods The color intensity resulting from the reaction of hydroxymethylfurfural, paratoluidine and barbituric acid was determined by reading the absorbance at a wavelength of 550 nm with a spectrophotometer. HMF measured spectrophotometrically was detected at very low levels in the syrup. Brix value, phenolic content and antioxidant values of fir syrup were also evaluated. Results Spectrophotometric analysis, the HMF content of traditional fir syrup was found to be very low, 8.1 mg/L. In addition, the total phenolic content value of locally produced fir cone syrup was found to be 6,050 mg GAE/g and the % inhibition value calculated by the DPPH method was 48,553, thus shedding light on its potential nutritional content through antioxidant activity analyses. Conclusions This study is the first to investigate fir syrup. As a result of the study, antioxidant activity analyzes shed light on its potential nutritional content. More importantly, this study was the first to show that fir syrup has a low glycemic index with a % Brix value (2.370±0.058) and that diabetic patients can safely use it instead of molasses.
Keywords: Zero hunger; Forestry Sciences (Other); Antioksidan aktivite; toplam fenolik madde; Kazdağı köknar şurubu; Hikroksimetilfurfural; Antioxidant activity; Total phenolic substance; Trojan Fir syrup; Hydroxymethylfurfural; Ormancılık (Diğer); 2. Zero hunger